Biohybrid Fibro-Porous Vascular Scaffolds: Effect of Crosslinking on Properties. Issue 1718 (2015) - Thomas, Vinoy; Nozik, Danna; Patel, Harsh; Singh, Raj K.; Vohra, Yogesh K.
ABSTRACT: Tubular grafts were fabricated from blends of polycaprolactone (PCL) and poly(glycolide-co-caprolactone) (PGC) polymers and coated with an extracellular matrix containing collagens, laminin, and proteoglycans, but not growth factors (HuBiogel™). Multifunctional scaffolds from polymer blends and membrane proteins provide the necessary biomechanics and biological functions for tissue regeneration. Two crosslinking agents, a natural crosslinker namely genipin (Gp) and a carbodiimide reagent namely 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC), were used for further stabilizing the protein matrix and the effect of crosslinking was evaluated for structural, morphological, mechanical properties using SEM, DSC and DMA. SEM images and fiber diameter distribution showed fiber-size between 0.2 μm to 1 μm with the majority of fiber diameters being under 500 nm, indicating upper range of protein fiber-sizes (for example, collagen fibers in extracellular matrix are in 50 to 500 nm diameter range). HB coating did not affect the mechanical properties, but increased its hydrophilicity of the graft. Overall data showed that PCL/PGC blends with 3:1 mass ratio exhibited mechanical properties comparable to those of human native arteries (tensile strength of 1-2 MPa and Young's modulus of <10 MPa). Additionally, the effect of crosslinking on coating stability was investigated to assure the retention of proteins on scaffold for effective cell-matrix interactions.